Microhabitat accessibility determines peptide substrate degradation by soil microbial community - Carlos Arellano-Caicedo; Pelle Ohlsson; Saleh Moradi; Edith C. Hammer (Microbiology Spectrum)
ABSTRACT Soil pore space, considered the most complex biomaterial that exists, generates a complex environment, that gives rise to a wide variety of properties, such as microbial diversity and carbon storage. Soils contain, at the same time, the largest carbon reservoir on earth and an immense amount of nutrient-limited microbial biomass. The reason why this carbon is not consumed by soil microbes is attributed to the complex nature of soil, which forms a labyrinth where carbon and microbes cannot be in direct contact. In the present study, by using microfluidics, we tested the effect of labyrinth-like structures of decreasing accessibility on the decomposing activity of soil microbial communities from a soil inoculum. The two parameters used to study the effect of microhabitat accessibility were either the turning angle in an array of channel-like pore structures or the fractal order in an array of maze-like pore structures. We found that in both cases, channels and mazes, decreasing accessibility produced a higher peptide substrate degradation. When we analyzed the degradation within the structures, we found that most of the activity is concentrated in the regions of intermediate accessibility. We think that the increased degradation activity in low accessibility mazes might be due to the reduced interactions within the microbial communities which leads to a reduction in competition. Lowered competition allows different communities with a wide range of metabolic strategies to cohabit in the structures, which resulted in a bulk increase of the peptide substrate degradation.IMPORTANCEThe role microbes have in the environment is highly influenced by the characteristics of their habitat. Here, we show that a complex habitat enhances the enzymatic activity of a soil microbial inoculum. This might occur due to a reduced competition in complex habitats, which allows a more diverse community to coexist and explore a wider variety of metabolic strategies. The different rates of enzymatic activity in different levels of complexity suggest emergent properties of microbial communities in complex microhabitats which could have important implication for microbial processes, such as soil carbon storage and nutrient cycling.